The Evolving Scope of Pharmacy Practice: From Medication Dispensing to Clinical Decision-Making (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The pharmacy profession has undergone a significant transformation over the past few decades, shifting from a traditional focus on medication dispensing to an expanded role in clinical decision-making and patient-centered care. This paper explores the historical context, current trends, and future directions of pharmacy practice, emphasizing the integration of pharmacists into interdisciplinary healthcare teams. Key areas of discussion include medication therapy management (MTM), pharmacogenomics, telehealth, and the impact of technological advancements. Regulatory changes, educational reforms, and global perspectives on pharmacy practice evolution are also examined.